13. OVERWEIGHT, OBESITY AND RELATED FACTORS AMONG STUDENTS OF UNIVERSITY OF MEDICINE AND PHARMACY AT HO CHI MINH CITY (Vietnam Journal of Community Medicine, 2024)
Objective: Determining the rate of overweight, obesity, and factors related to this condition among students of the University of Medicine and Pharmacy at Ho Chi Minh City (UMP).Methods: A cross-sectional study was conducted from February to May 2024 among students of the UMP based on the structured questionnaire including anthropometric index (height, weight), personal and family.Results: Students with overweight, and obesity were 41,7%; in which the rate of overweight is 23,4% and obesity is 18,3%. Factors with a statistically significant relationship (p
Keywords: Overweight, obesity, sugar-sweetened beverage consumption, related factors, university students